Pengaruh Komunikasi, Lingkungan Kerja, dan Beban Kerja terhadap Kepuasan Kerja Karyawan pada Perusahaan untuk Meningkatkan Kinerja dan Produktivitas Organisasi: Studi Pada Karyawan PT Indomarco Prismatama - Farah Tasya Untari; Koen Hendrawan (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the effect of communication (X1), work environment (X2), and workload (X3) on job satisfaction (Y) among employees at PT Indomarco Prismatama. Job satisfaction is a crucial factor influencing employee performance and productivity; therefore, understanding the factors that affect it is essential for the company’s sustainability and growth. This research employs a quantitative approach with a saturated sampling technique, in which the entire population is used as the sample. The total number of respondents in this study was 30 employees. The analytical method used was path analysis with the assistance of SPSS version 22 software. The results show that the communication variable (X1) has a significant effect on job satisfaction (Y), with a significance value of 0.000. This indicates that effective, clear, and open communication between management and employees can enhance employees’ satisfaction with their jobs. Furthermore, the work environment variable (X2) also has a significant effect on job satisfaction (Y), with a significance value of 0.000. This finding suggests that a safe, comfortable, and supportive work environment, both physically and non-physically, plays a vital role in shaping employees’ positive perceptions of their work. In addition, the workload variable (X3) has a significant effect on job satisfaction (Y), with a significance value of 0.009. This means that a proportional workload, in accordance with employees’ capabilities, can improve job satisfaction, whereas excessive workloads may reduce it. Overall, this study concludes that communication, work environment, and workload have a significant effect on job satisfaction among employees at PT Indomarco Prismatama. The implication of this study is that management should continuously improve the quality of communication, create a conducive work environment, and establish a balanced workload to maintain and enhance employee job satisfaction.